2022
DOI: 10.3390/ijms23105738
|View full text |Cite
|
Sign up to set email alerts
|

Structural Bases of Prion Variation in Yeast

Abstract: Amyloids are protein aggregates with a specific filamentous structure that are related to a number of human diseases, and also to some important physiological processes in animals and other kingdoms of life. Amyloids in yeast can stably propagate as heritable units, prions. Yeast prions are of interest both on their own and as a model for amyloids and prions in general. In this review, we consider the structure of yeast prions and its variation, how such structures determine the balance of aggregated and solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 139 publications
(212 reference statements)
0
2
0
Order By: Relevance
“…Sup35C contains GTP-binding motifs and interaction sites with various proteins including eRF1 (see [33] for a recent review). [PSI + ] remains the most studied yeast prion, widely used to characterize various aspects of prion biology, including the existence of different strains or variants (see [15] for recent review).…”
Section: Prions Discovered By Their Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…Sup35C contains GTP-binding motifs and interaction sites with various proteins including eRF1 (see [33] for a recent review). [PSI + ] remains the most studied yeast prion, widely used to characterize various aspects of prion biology, including the existence of different strains or variants (see [15] for recent review).…”
Section: Prions Discovered By Their Phenotypementioning
confidence: 99%
“…Since then, many new prions and prion-like proteins have been identified in yeast. Several recent reviews have focused on yeast prions [11][12][13][14][15][16][17][18][19]. Here, we provide a brief overview of the yeast prions found so far and focus our attention to the various approaches used to identify them.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1994, there have been a diverse array of yeast proteins identified that undergo a structural conversion that is epigenetically heritable through many rounds of cell division, defining them as prions (reviewed in [ 5 , 6 ]). Some of the most recently identified prions are not amyloid in nature [ 7 9 ], whereas others, especially the earliest identified yeast prions, are amyloids.…”
Section: The Sup35 Prion Called [ Psi + ]mentioning
confidence: 99%
“…It's also worth mentioning that a major contribution to the understanding of the mechanisms underlying the influence of chaperones on amyloidogenesis has been made by studying these processes in yeast, which possesses its own prion protein Sup35 and a set of chaperones [58]. Although yeast models are only remotely relevant to the occurrence of prion diseases in animals, such models are conveniently used to identify general patterns of chaperone effects on the amyloid transformation of proteins [59,60]. In addition, the expression of mammalian amyloid proteins in yeast cells allows these models to be approximated by those based on mammalian cells [61].…”
Section: The Role Of Chaperones In the Pathological Transformation Of...mentioning
confidence: 99%